The Creativity of Islamic Religious Education Teachers for Effective Learning - Fauzan, Farhan Ahmad; Hasbiyallah, Hasbiyallah; Fikri, Miftahul (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2022)
Learning in schools currently cannot be effective due to the lack of organized learning by the teacher. This study was to determine the effect of the creativity of Islamic Religious Education teachers in Elementary Schools or Madrasah Ibtidaiyah on effective learning. The research method is a quantitative method with a post-positivist approach. The population in this study was 25 teachers of Islamic education at the Elementary School or Madrasah Ibtidaiyah in the city of Bandung. While the sample is 18 teachers. Data collection through questionnaires. The data analysis technique used data normality test and correlation test. Hypothesis testing using a  path analysis of 0.05. The results of the normality test of the data showed that the data were normally distributed, which was indicated by the distribution of the points on the Q-Q diagram on a diagonal line in both the teacher creativity test and effective learning. The results of the correlation test show that there is a positive relationship between teacher creativity in realizing effective learning with a coefficient of 0.522. The conclusion from the results of this study is that there is an influence of teacher creativity in an effort to realize effective learning. So the more Islamic Religious Education teachers increase their creativity, the higher the chances of realizing effective learning.Pembelajaran di sekolah saat ini belum bisa efektif dikarenakan kurang terorganisirnya pembelajaran oleh Guru.Penelitian ini bertujuan untuk mengetahui pengaruh kreativitas guru Pendidikan Agama Islam di Sekolah Dasar/ Madrasah Ibtidaiyah terhadap pembelajaran efektif. Metode penelitian ini adalah metode kuantitatif dengan pendekatan post-positivisme. Populasi dalam penelitian ini adalah 25 orang guru pendidikan Agama Islam di Sekolah Dasar atau Madrasah Ibtidaiyah di Kota Bandung. Sedangkan sampel nya adalah 18 guru. Pengumpulan data melalui angket. Teknik analisis data menggunakan uji normalitas data dan uji kolerasi. Pengujian hipotesis menggunakan analisis jalur 0,05. Hasil penelitian uji normalitas data menunjukkan data yang berdistribusi normal yang ditujukkan oleh sebaran titik-titik pada diagram Q-Q berada pada garis diagonal baik pada uji kreativitas guru maupun pembelajaran efektif. Hasil uji kolerasi menunjukan terdapat hubungan yang positif antara kreativitas guru terhadap pembelajaran efektif dengan koefesien sebesar 0,522. Kesimpulan dari hasil penelitian ini adalah terdapat pengaruh kreativitas guru dalam usaha mewujudkan pembelajaran efektif. Maka semakin guru Pendidikan Agama Islam meningkatkan kreativitas nya, semakin tinggi peluang untuk mewujudkan pembelajaran yang efektif.